Pedogenesis And Characterization Of Some Soils From The Chalan Beel Of Bangladesh - Islam, ABMS; Khan, ZH; Mazumder, AR (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Twenty two soil samples from four pedons representing some established soil series namely Jaonia, Haiti, Taras and Digli from the Chalan beel area of Bangladesh were studied in the field as well as in the laboratory for their pedogenesis and characterization. All the soils are heavy textured with clay contents ranging from 47 to 60 percent. The soils are moderately acidic to neutral in reaction with high base saturation. The soils have developed redoximorphic features including redox concentration and redox depletion due to periodic flooding more than 4 months in the monsoon season. Development of cambic horizon in these soils is the most notable morphogenetic feature. Gleization and weak hydromorphism are the dominant pedogenic processes. At the subgroup level the soiis were classified as Typic Endoaquepts and Aerie Endoaquepts. Finally the soiis are characterized at the family level of soil taxonomy. Asiat. Soc. Bangladesh, Sci. 40(2): 271-281, December 2014